Tick-Borne Flaviviruses Depress AKT Activity during Acute Infection by Modulating AKT1/2 - Joshua M. Kirsch; Luwanika Mlera; Danielle K. Offerdahl; Marthe VanSickle; Marshall E. Bloom (Viruses, 2020)
Tick-borne flaviviruses (TBFVs) are reemerging public health threats. To develop therapeutics against these pathogens, increased understanding of their interactions with the mammalian host is required. The PI3K-AKT pathway has been implicated in TBFV persistence, but its role during acute virus infection remains poorly understood. Previously, we showed that Langat virus (LGTV)-infected HEK 293T cells undergo a lytic crisis with a few surviving cells that become persistently infected. We also observed that AKT2 mRNA is upregulated in cells persistently infected with TBFV. Here, we investigated the virus-induced effects on AKT expression over the course of acute LGTV infection and found that total phosphorylated AKT (pAKT), AKT1, and AKT2 decrease over time, but AKT3 increases dramatically. Furthermore, cells lacking AKT1 or AKT2 were more resistant to LGTV-induced cell death than wild-type cells because they expressed higher levels of pAKT and antiapoptotic proteins, such as XIAP and survivin. The differential modulation of AKT by LGTV may be a mechanism by which viral persistence is initiated, and our results demonstrate a complicated manipulation of host pathways by TBFVs.